Eficacia de diferentes técnicas para reducir el estrés: estudio en docentes de Guayaquil que cursan un doctorado (Estudios) - Arévalo Avecillas, Danny (2017)
The following research aims to identify the effectiveness of three techniques to reduce stress in a population sample of adults teachers of the Catholic University of Santiago de Guayaquil ( UCSG ) and the Escuela Superior Politecnica del Litoral (ESPOL ) who teach and enrolled a doctoral program in Strategic Business Administration from the Pontificia Universidad Catolica del Peru . The research has a quantitative approach that allowed measurement of percentage terms the gathering of information. The population of this study is obtained that deep breathing and progressive relaxation are more effective in men and the imaging technique is best for woman.